Cross-sector Partnerships Models in Corporate Social Responsibility to Implement Poverty Reduction Initiatives in Indonesia - Edi, Ashari Cahyo (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2015)
In order to effectively align corporate social responsibility (CSR) with the poverty reduction agenda, corporations need to be more inclusive and collaborative with other actors. Cross-sector partnerships in the implementation of CSR have been an emerging approach and practice, as promoted by public administration scholars. Key actors in the partnerships may come from the government, civil society represented by non-governmental organizations (NGOs), and corporations. However, designing successful effective partnerships that are relevant to cross-sector dynamics and political contexts has been proven to be particularly challenging, especially in emerging economies and new democracies, such as Indonesia. This paper provides key characteristics of effective cross-sector partnerships that have been derived from an examination of three case studies in Indonesia and Tanzania. They represent cross-sector partnerships with differing scope and depth. Throughout this paper, one can observe and extract key characteristics of effective partnerships based on three case studies of which a model for each is described. In particular, characteristics utilized for assessing the effectiveness of the models include ownership, alignment and synchronization, accountability, reduced dependency, resource sharing, along with representation and legitimacy.